Pengaruh Latihan Senam Aerobik Low Impact terhadap Penurunan Persentase Lemak Tubuh dan Peningkatan Massa Otot - Siska Siska; Bafirman Bafirman; Sri Gusti Handayani; Zamhar Bakri (Jurnal Sporta Saintika, 2026)
This study aims to determine the effect of low-impact aerobic exercise on reducing body fat percentage and increasing muscle mass. The main problem in this study is a sedentary lifestyle and irregular eating patterns that trigger fat accumulation and decrease muscle mass. The research method used is a quasi-experiment. The population was 25 people, and a sample of 18 members of Ozone Fitness and Aerobics with a purposive sampling technique. The measurement instruments included a skinfold caliper for body fat percentage and a digital scale, Innerscan Tanita BC-541 body composition for muscle mass. Data were analyzed using a t-test with a significance level of α = 0.05. The results showed that: (1) Low Impact aerobic exercise has a significant effect on body fat percentage, t count 8.53 > t table 1.74, the average value of the pretest 36.73%, and the posttest 35.24%. There was a decrease of 1.49%, (2) Low-impact aerobic exercise had a significant effect on muscle mass, t count 11 > t table 1.74, the average pretest value was 37.47, and posttest 37.65. There was an increase of 0.18.